Planilhas eletrônicas no ensino de matemática : análise de uma proposta didática para o ensino médio - Tartari, Vildomar Luiz (2016)
This work belongs to the line of research information technologies, communication and interaction applied to the teaching of Science and Mathematics, from the Graduate Program in Science and Mathematics Teaching and seeks to answer the following questions: To what extent the available technology in society in the case of this study, spreadsheets, contribute to the process of teaching and learning mathematical concepts? How the use of educational technologies associated with everyday situations, provide social interaction? Such questions have defined the purpose of the present study to investigate the potential use of spreadsheets in the approach of mathematical concepts, structured from real life experiences of the students. Therefore, research focused on application-oriented teaching sequence to facilitate the construction of knowledge in a cognitive and structured approach to enhance the use of technology in the teaching and learning of Mathematics was outlined. In addition, the study emphasized the importance of using the daily life and social interaction, especially relying on the meaning of Vygotsky. As theoretical support, the study rescued other research in the area of the use of technology in mathematics education, and reflected and analyzed the data collected in the light of cognitivism and social interaction. In terms of method, the study used a qualitative research in view of Triniños (1994), establishing categories according to the proposed by Bardin (2004). Finally, the study showed the feasibility of didactic proposal and stressed its importance as favoring learning in mathematics for students of the 1st year of high school. Such viability was analyzed considering the perception of the teacher / researcher and students, whose results showed that address mathematical concepts through technology involving contextualized situations helps students to understand that mathematics constitutes a significant body of knowledge and present in the life of the subjects. Attached to this dissertation, its educational product developed as supporting document, entitled "Use of spreadsheets for teaching mathematics: activity suggestions for basic education"